Education as prevention: Intersectional feminism in security spaces - Elliott, Kathlyn; Benjamin, Saija; Kuusisto, Arniika; Koirikivi, Pia (JSSE - Journal of Social Science Education, 2023)
Purpose: This article argues that the inclusion of education in prevention creates space to address long standing concerns about the racialized and gendered problems created by traditional security approaches Design/methodology/approach: The article uses intersectional feminism as it’s theoretical lens/basis. Findings: Education can be a space that allows for more women, non-binary persons, and people of color to engage as policy actors in the prevention of violent extremism. While policy documents emphasize the role education plays, and alludes to the presence of women, non-binary persons, and people of color in education, the research and application often overlooks these perspectives.